Biotechnology A Textbook of Industrial Microbiology - Crueger, Wulf Crueger, Anneliese (Panima Publishing Corporation, 2000)
An up-to-date textbook that presents the key principles and major processes of industrial microbiology. This edition includes new material on genetic engineering, including the use of recombinant DNA techniques for strain selection and for the production of proteins, enzymes and amino acids.